2019
DOI: 10.1111/josh.12824
|View full text |Cite
|
Sign up to set email alerts
|

Use of the School Setting During the Summer Holidays: Mixed‐Methods Evaluation of Food and Fun Clubs in Wales

Abstract: OBJECTIVE School summer holiday clubs in deprived areas of Wales were evaluated to examine opportunities for healthy eating and physical activity and explore delivery processes. METHODS Ten Food and Fun clubs participated in 2016. Quantitative data (child and parent surveys; N = 196, N = 84) assessed the opportunity to provide children with breakfast and lunch. A sub‐sample of children wore an accelerometer (N = 41) to evaluate the opportunity for achieving 1‐hour of moderate to vigorous activity (MVPA) at clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Previous academic research has investigated the benefits and issues of holiday provision from the views of staff delivering holiday provision and attendees of holiday clubs, and identified outcomes in terms of health and wellbeing for children as well as parents, staff and volunteers (Defeyter et al, 2015;Graham et al, 2016;Holley et al, 2019;Morgan et al, 2019). Moreover, recent research identified that holiday clubs relied upon networks and connections with other civil society organizations to deliver holiday provision (Stretesky et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous academic research has investigated the benefits and issues of holiday provision from the views of staff delivering holiday provision and attendees of holiday clubs, and identified outcomes in terms of health and wellbeing for children as well as parents, staff and volunteers (Defeyter et al, 2015;Graham et al, 2016;Holley et al, 2019;Morgan et al, 2019). Moreover, recent research identified that holiday clubs relied upon networks and connections with other civil society organizations to deliver holiday provision (Stretesky et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent research identified that holiday clubs relied upon networks and connections with other civil society organizations to deliver holiday provision (Stretesky et al, 2020). Nevertheless, there is a gap in the literature on the implementation of holiday provision and the adaption and fidelity of providing food provision within community and school based settings (Graham et al, 2016;Holley et al, 2019;Morgan et al, 2019). As the development of holiday clubs continues, there is a need to examine the views of senior stakeholders responsible for facilitating and implementing holiday provision.…”
Section: Introductionmentioning
confidence: 99%
“…Staff emphasised that holiday clubs are not just about providing food, “ it's about getting involved and then learning those essential life skills ” and “ it's about being proactive and empowering them ” (P7, Programme Manager). Previous research has found that holiday clubs provide a range of health, wellbeing, and developmental opportunities to children and families including alleviating hunger ( 17 ), reducing social isolation ( 21 ), enhancing social skills ( 22 ), and promoting healthy eating ( 23 ) and physical activity ( 21 ). Holiday clubs enable these opportunities by providing a wealth of services including food, entertainment equipment, sport, physical activity, fun days out, information and education ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Non-DfE funded holiday programmes are therefore also essential to protect families outside of the DfE targeted areas and yet it is currently unknown how many non-DfE funded programmes are operating. Nevertheless, prior to Covid-19 research suggested that holiday clubs have a range of benefits including alleviating hunger ( 17 ), reducing social isolation ( 21 ), enhancing social skills ( 22 ), and promoting healthy eating ( 23 ) and physical activity ( 21 ). Similarly, holiday clubs provide a wealth of services including material goods (e.g., food and entertainment equipment), sport, physical activity, fun days out, information and education ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…In response to concerns about children experiencing holiday food insecurity, community groups, local authorities, schools and faith groups have established holiday clubs in economically deprived neighborhoods to provide free food and activities to children during the school holidays. Recent research on holiday provision has demonstrated a need to support families as a result of the increased financial hardship and risk of isolation during the school holidays (Graham et al, 2016, Mann et al, 2020 and identified a range of social, wellbeing, and health benefits for attendees (Defeyter et al, 2015;Graham et al, 2016;Holley et al, 2019;Morgan et al, 2019). More recently, governments across the devolved nations of the UK have pledged funding to support programs of holiday provision, albeit these funding initiatives vary in scale and are not evenly distributed among disadvantaged communities (Mann et al, 2018).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%